(untitled) (Nepalese Journal of Hospitality and Tourism Management, 2025)
The Paudur village is situated on Paudur ridge above 1200 m high from sea level. The panoramic view of the Himalayas in the north, the hills and knolls seen in the east, west and south, and the bird’s eye view of the intermontane Pokhara valley and Phewa Lake at arm’s stretch allure people towards it. Once it was a farm village transformed into ‘a ghost village’ when the major trekking route to Jomsom from Pokhara opportune local community to open hotels and cater meals and accommodation to the travellers. The Pokhara-Baglung highway changed the whole scenario along the trekking route and the lucrative hotel business disappeared for good. Although a large open space, very rich natural scenery, accessibility to the market, enough drinking water, power/electricity, and security are available there, no tourist-based activities like hotels, restaurants, resorts and recreational spots are seen here. This paper has tried to describe the factors that are available to boost the tourism potential of this village.